DESAIN PERMAINAN BERBASIS KARPET SENSORIS UNTUK MENSTIMULASI PERKEMBANGAN MOTORIK HALUS PADA BALITA - Riefya, Aisyah Fadhilla; Bahalwan, Hamdan (Narada : Jurnal Desain dan Seni, 2022)
Growth and development starts from infancy and stops as adults. Child development can be seen from motoric, social and emotional development, WHO states that more than 200 million children under the age of five in the world do not fulfill the potential of child development. Many factors can help develop toddler development, children need the right stimulus according to their age. For this reason, a sensory carpet design was made that can stimulate children's growth and development and educate parents about the importance of stimulating motor development in children. This study uses a mixed method, which combines qualitative research and quantitative research. This sensory carpet game can help parents stimulate fine motor development in children through games of inserting a rope into a hole, opening a zipper game, a button game and a color match game. The concept applied to this game is learning with fun, with a forest theme to introduce animals and plants in the forest, as well as introducing children to textures that represent these animals and plants. In addition, this game was created to provide a choice of educational games for toddlers, so parents do not give gadgets to children.